Bioadhesion, Antimicrobial Activity, and Biocompatibility Evaluation Bacterial Cellulose Based Silver Nanoparticle Bioactive Composite Films - Çiftçi, Fatih (Elsevier, 2024)
Bioactive and biocompatible BC/AgNP composite films were synthesized by loading silver nanoparticle (AgNP) into bacterial cellulose (BC) fibrils. Physicochemical analyses (FTIR, TGA-DSC, SEM-EDS, TEM, XRD) and mechanical tests were performed on the synthesized BC fibril and BC/AgNP composite films. Young’s Modulus, Tensile strength, Elongation at break, Compressive strength and Stiffness of (45% moisture) BC/AgNP composite films were found to be 253.2 ± 2.01 MPa, 13.7 ± 1.40 MPa, 21.4 ± 1.67%, 47.17 ± 8.98 MPa, 1.05 ± 2.32 GPa and 519.88 ± 81.51 (Units), respectively. Moreover, the high-water retention capacity of BC fibril structures was supported by the contact angles and swelling profiles observed in BC/AgNP composite structures. Further, the bioadhesion performance of BC/AgNP composite films was evaluated ex vivo on chicken skin and it was observed that the presence of AgNP played an active role in the adhesion behavior of the composite films. It was also observed that the synthesized BC/AgNP composite films exhibited bactericidal behavior against pathogens (Staphylococcus aureus and Pseudomonas aeruginosa) and had a high bactericidal effect. Biocompatibility tests of the composite films were evaluated by using L929 mouse fibroblast cells. The cell nucleus wall staining (Mitored and Dio6) and fluorescence visualization studies were performed to investigate the biocompatibility behavior of BC/AgNP composite films. The results showed that BC/AgNP composite films did not any cytotoxic effect and allowed epidermal cells to adhere and grow. Overall, obtained results showed that the synthesized biocompatible BC/AgNP composite films are suitable to be used as wound dressings in tissue engineering applications and may be used as a bioactive material that can reduce inflammation in skin barriers and promote wound healing.
Keywords: Bacterial cellulose; Silver nanoparticle; Composite film; Bioadhesion; Biocompatibility